How Micropatterning and Surface Functionalization Affect the Wetting Behavior of ZnO Nanostructured Surfaces. Issue 13 (29th March 2016) - Laurenti, Marco; Verna, Alessio; Fontana, Marco; Stassi, Stefano; Canavese, Giancarlo; Marasso, Simone L.; Cauda, Valentina
Abstract : Smart surfaces with a tunable wetting behavior between superhydrophobic and superhydrophilic states are of great interest for different applications, such as novel self‐cleaning/antifogging layers, or in view of the development of microfluidic devices and chemical/biochemical sensors of new generation. This work shows the tuning of the wetting behavior of hydrothermally grown zinc oxide nanowires (NWs) by combining the dual effect resulting from either surface chemical functionalization of the NWs and their growth on substrates prepatterned with different micro‐sized geometries. The characterization results highlight that vertically aligned ZnO NWs successfully cover all the microfeatures of the patterned substrates and can be successfully functionalized with aminopropyl groups. This chemical functionalization drives the initial transition of as‐prepared, superhydrophilic ZnO NWs toward a superhydrophobic regime. Then, protonation/deprotonation of amine groups, induced by their interaction with acid or basic media, changes the wetting state of ZnO NWs between hydrophilic and hydrophobic regimes. Reversible and successful switching from hydrophobic to hydrophilic states can be achieved under ad hoc conditions, in particular using appropriate micropatterns that do not favor the formation and entrapment of air bubbles. Abstract : The wetting behavior of zinc oxide nanowires (NWs) can be tuned between superhydrophobic and superhydrophilic states by combining surface chemical functionalization and prepatterned substrates. Protonation/deprotonation of amine‐groups interacting with acidic or basic media induces the ZnO NW wetting transition. The reversibility is promoted by ad‐hoc pattern geometries, preventing the entrapment of air bubbles.